Визначення кількісних показників віджиму технічних олій при використанні пристрою остаточного формування паливного брикету - Самойчук, Кирило Олегович; Самохвал, Віталій Анатолійович; Samoichuk, Kyrylo; Samokhval, Vitalii (Запоріжжя : ТДАТУ, 2024)
UA: Аналіз досліджень показав, що при використанні багатосекційного пристрою остаточного формування паливних брикетів з оліємісткої сировини, значно поліпшується якість готової продукції завдяки контрольованого відводу технічних олій на певних етапах формування. За рахунок подовженої конструкції пристрою збільшився час перебування сировини в стиснутому стані, що в свою чергу підвищило якість кінцевого продукту. При застосуванні даної технології брикетування, саме обладнання має значно більший ресурс ніж в аналогів, тому що відбувається незначний відбір олій на етапах де максимальне тертя та збільшується на етапах з мінімальним, за рахунок чого, як показала практика, ресурс обладнання збільшується в декілька раз. Виконання вхідної частини матриці у формі конуса сприяє кращому формуванню різних видів сировини та зниженню енергоємності самого процесу, а збільшення відношення довжини набору секцій до його діаметру збільшує тиск при формуванні брикету та покращує відвід олій. Дане обладнання добре себе зарекомендувало в промислових умовах, та зазнає постійних вдосконалень та покращень. EN: The analysis of the research showed that when using a multi-sectional device for the final formation of fuel briquettes from oil-containing raw materials, the quality of the finished product is significantly improved due to the controlled removal of industrial oils at certain stages of formation. Due to the design features of the device, the time spent by the raw material in the compressed state has increased, which in turn has also improved the quality of the final product. When applying this technology, the equipment has a much longer service life than its analogues, since there is a slight selection of oils at the stages with maximum friction and increases at the stages with minimal friction, due to which, as practice has shown, the service life of the equipment increases several times. This research is aimed at overcoming the problem of excessive oil content in the finished product, as this problem is faced by most fuel briquette producers who work with oil-containing waste from sunflower, flax, soybean, rapeseed and other crops. The main goal of our work is to improve the quality of finished products through controlled selection of oils and increase the time of raw materials in the compressed state, as well as reduce the cost of finished products without losing quality. When developing methods for solving this problem, the designs and patents of well-known screw-type press equipment were studied. In the new equipment, it was decided to make the inlet part of the die in the form of a cone with rotation protection ribs, which in turn contributed to better forming of different types of raw materials and reduced energy consumption of the process itself, and an increase in the ratio of the length of the set of sections to its diameter increases the pressure during briquette formation and better drainage of industrial oils. This equipment has proven itself in industrial conditions and is constantly being improved. When the device is used in conjunction with a screw extruder, the cost of the finished product is reduced in the range of 5...20%, depending on the type and structure of the raw material.
Determination of quantitative indicators of squeezing of industrial oils when using the device for final formation of fuel briquettes
Keywords: брикет; прес; олії; формування; дожимний пристрій; briquette; press; oils; molding; final forming device